The prevalence of Clostridioides difficile on farms, in abattoirs and in retail foods in Ireland. (September 2021) - Marcos, Pilar; Whyte, Paul; Rogers, Thomas; McElroy, Máire; Fanning, Seamus; Frias, Jesus; Bolton, Declan
Abstract: An increasing proportion of Clostridioides difficile infections (CDI) are community acquired. This study tested farm, abattoir and retail food samples for C. difficile, using peer reviewed culture and molecular methods. The contamination rate on beef, sheep and broiler farms ranged from 2/30 (7%) to 25/30 (83%) in faeces, soil and water samples, while concentrations ranged from 2.9 log10 cfu/ml to 8.4 log10 cfu/g. The prevalence and associated counts were much lower in abattoir samples. Although 26/60 were C. difficile positive by enrichment and PCR, only 6 samples yielded counts by direct plating (1.1 log10 cfu/cm 2 to 5.1 log10 cfu/g). At retail, 9/240 samples were C. difficile positive, including corned beef (1), spinach leaves (2), iceberg lettuce, little gem lettuce, wild rocket, coleslaw, whole milk yogurt and cottage cheese (1 sample each), with counts of up to 6.8 log10 cfu/g. The tcdA, tcdB, cdtA, cdtB, tcdC and tcdR genes were detected in 41%, 99.2%, 33.6%, 32%, 46.7% and 31.1%, respectively, of the 122 C. difficile isolates obtained. It was concluded that although the prevalence of C. difficile decreased along the food chain, retail foods were still heavily contaminated. This pathogen may therefore be foodborne, perhaps necessitating dietary advice for potentially vulnerable patients. Highlights: C. difficile contamination rates of the farm samples tested ranged from 7 to 83%. Approximately half of abattoir samples were positive with counts up to 5.1 log10 cfu/g. C. difficile was detected in 9/240 retail food samples at concentrations of up to 6.8 log10 cfu/g. C. difficile isolates were positive for the toxin B gene ( tcdB ) in 99.2% of the cases.